2023
DOI: 10.3390/antiox12051136
|View full text |Cite
|
Sign up to set email alerts
|

Crop, Host, and Gut Microbiome Variation Influence Precision Nutrition: An Example of Blueberries

Abstract: Epidemiological studies have shown associations between polyphenol-rich fruit intake and bone health, and preclinical studies have shown that blueberries improve bone health. To determine the genotype and dose of blueberries that are effective in ameliorating age-related bone loss, a multi-institutional team of investigators performed in vitro, preclinical, and clinical studies on blueberry varieties that differed in flavonoid profiles. Principal component analysis was used to select blueberry genotypes that v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Additionally, it has been shown that the bioavailability of polyphenolic compounds in rats was not predicted by the TPC [ 67 ], further increasing the complexity of predicting the dose-biological response relationship. An example is the impact of blueberry on rat gut microbiome diversity, which seems to be dose-dependent [ 67 ]. It has been acknowledged that dietary phytochemicals can act as hormetins [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, it has been shown that the bioavailability of polyphenolic compounds in rats was not predicted by the TPC [ 67 ], further increasing the complexity of predicting the dose-biological response relationship. An example is the impact of blueberry on rat gut microbiome diversity, which seems to be dose-dependent [ 67 ]. It has been acknowledged that dietary phytochemicals can act as hormetins [ 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, while Yousef et al (2013) showed blueberry TPCs ranging from 1.63 to 2.87 mg (GAE)/g [66], Weaver et al (2023) reported that the weight of blueberry powder needed to achieve the same dose of TPC (25 mg/kg BW) varied from 189 to 285 mg [67]. Additionally, it has been shown that the bioavailability of polyphenolic compounds in rats was not predicted by the TPC [67], further increasing the complexity of predicting the dose-biological response relationship. An example is the impact of blueberry on rat gut microbiome diversity, which seems to be dose-dependent [67].…”
Section: Discussionmentioning
confidence: 99%
“…Disadvantages of the use of bioactive compounds or foods include the variation in the active agents, if indeed the active agent is known. Using blueberry as an example, the variation in blueberry polyphenolics from the food crop through processing to health outcomes of individuals who vary in genetics and their gut microbiome was reported in a previous study 199 . The dramatic variation in polyphenolic profiles among genotypes of blueberry and subsequent variation in polyphenol metabolism, variation in the gut microbiome with blueberry dose, and variation in the female response compared with the male response to blueberry consumption on bone illustrate that one individual study with defined bioactive materials and a particular study population may not be generalizable to all blueberries Bold Polyphenol and bone health.…”
Section: Diet and Bone Healthmentioning
confidence: 98%
“…Accumulating evidence suggests that foods rich in phenolic compounds, such as prunes, blueberries, and soybeans may be effective in protecting against postmenopausal bone loss (3). The exact mechanisms underlying the osteoprotective effects of phenolic-rich foods and supplements are largely unknown but are thought to be partly attributed to the ability of host and/or microbial phenolic metabolites to alter endogenous antioxidant capacity, to exert antiinflammatory effects, or to provide prebiotic-like modulation of the gut microbiome (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%